HUBUNGAN ANTARA PERCAYA DIRI DAN MOTIVASI BELAJAR IPA SISWA: STUDI PADA KELAS V SDN 96 CITTA KECAMATAN CITTA KABUPATEN SOPPENG - Sudarto Sudarto; Achmad Shabir; Andi Ahlal Herman (Jurnal Inovasi Penelitian, 2022)
This study was a correlational study that aimed to determine whether there was or there was not a coorelation between self-confidence and Science learning motivation of the 5th Grade students at SDN 96 Citta, Citta District, Soppeng Regency. The variables in this study were students' self-confidence and students' Science learning motivation The population in this study were all fifth grade students at SDN 96 Citta, Citta District, Soppeng Regency, in a count 31 students. The sampling technique in this study wais a non-probability sampling technique with the type of total sampling or saturated sampling. The data analysis technique used descriptive statistics and inferential statistics. Based on the results of inferential statistical analysis, it was obtained that t count (3.4513) > t table (2.04523) at a significance level of 0.05 so that H1 was accepted and H0 was rejected. Thus, it could be concluded that there was a significant correlation between self-confidence and science learning motivation of fifth grade students at SDN 96 Citta, Citta sub-district, Soppeng Regency.